Evaluation of the Formulation Parameter-Dependent Redispersibility of API Nanoparticles from Fluid Bed Granules - Martin Wewers; Jan Henrik Finke; Stefan Czyz; Bernard Van Eerdenbrugh; Edgar John; Guido Büch; Michael Juhnke; Heike Bunjes; Arno Kwade (MDPI AG, 2022)
The production of nanosuspensions of poorly soluble active pharmaceutical ingredients (API) is a popular technique to counteract challenges regarding bioavailability of such active substances. A subsequent drying of the nanosuspensions is advantageous to improve the long-term stability and the further processing into solid oral dosage forms. However, associated drying operations are critical, especially with regard to nanoparticle growth, loss in redispersibility and associated compromised bioavailability. This work extends a previous study regarding the applicability of an API (itraconazole) nanosuspension as a granulation liquid in a fluidized bed process with focus on the influence of applied formulation parameters on the structure of obtained nanoparticle-loaded granules and their nanoparticle redispersibility. Generally, a higher dissolution rate of the carrier material (glass beads, lactose, mannitol or sucrose) and a higher content of a matrix former/hydrophilic polymer (PVP/VA or HPMC) in the granulation liquid resulted in the formation of coarser and more porous granules with improved nanoparticle redispersibility. HPMC was found to have advantages as a polymer compared with PVP/VA. In general, a better redispersibility of the nanoparticles from the granules could be associated with better dispersion of the API nanoparticles at the surface of the granules as deduced from the thickness of nanoparticle-loaded layers around the granules. The layer thickness on granules was assessed by means of confocal Raman microscopy. Finally, the dispersion of the nanoparticles in the granule layers was exemplarily described by calculation of theoretical mean nanoparticle distances in the granule layers and was correlated with data obtained from redispersibility studies.